Black Box Testing in Community Service Systems Using Boundary Value Analysis and Cause Effect Graph Methods (Case Study of Jombang District Community and Village Empowerment Service) - Eka Zuni Selviana; Henni Endah Wahanani; Firza Prima Aditiawan (East Asian Journal of Multidisciplinary Research, 2023)
The community service information system at the Jombang Regency Community and Village Empowerment Service is an accurate and interactive information medium for the community and has been integrated with the village fund management system. So it is necessary to maintain the quality of the system so that it runs according to the expected functionality and runs optimally. Testing focuses on system functionality and performance using Black Box Testing with Bodary Value Analysis and Cause Effect Graph methods. Based on the test results, the use of Cause and Effect Graphs in public service information systems is more dominant for testing data entry features, and features in the form of buttons. Meanwhile, Boundary Value Analysis is more dominant in testing features that have a range such as name or title input, caption input, and complaint message input and obtained an effectiveness value of 77.86%, which is in the quite effective category and still needs to be done. improved and developed so that the system can be successful. achieve maximum effectiveness values ​​so that functionality runs more optimally.